2003
DOI: 10.1074/jbc.m303073200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Importance of the Carboxyl-terminal Region of Striated Muscle Tropomyosin

Abstract: Striated muscle tropomyosin (TM) interacts with actin and the troponin complex to regulate calcium-mediated muscle contraction. Previous work by our laboratory established that ␣-and ␤-TM isoforms elicit physiological differences in sarcomeric performance. Heart myofilaments containing ␤-TM exhibit an increased sensitivity to calcium that is associated with a decrease in the rate of relaxation and a prolonged time of relaxation. To address whether the carboxyl-terminal, troponin T binding domain of ␤-TM is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 20 publications
3
56
0
Order By: Relevance
“…A markedly increased expression of β-TM in mouse hearts (α-TM to β-TM ratio of approximately 1:4) leads to the death of animals soon after birth, along with severe cardiac abnormalities in both contraction and relaxation (197). However, the overexpression of the wild type α-TM in the heart does not lead to any morphological or physiological alterations in cardiac performance (200). A potential mechanism for the difference in function between these two isoforms, which are 86% identical, is likely in their interaction with the neighbouring thin filament molecules.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…A markedly increased expression of β-TM in mouse hearts (α-TM to β-TM ratio of approximately 1:4) leads to the death of animals soon after birth, along with severe cardiac abnormalities in both contraction and relaxation (197). However, the overexpression of the wild type α-TM in the heart does not lead to any morphological or physiological alterations in cardiac performance (200). A potential mechanism for the difference in function between these two isoforms, which are 86% identical, is likely in their interaction with the neighbouring thin filament molecules.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…A potential mechanism for the difference in function between these two isoforms, which are 86% identical, is likely in their interaction with the neighbouring thin filament molecules. Thus, TM isoform shift may account for weaker binding of fast skeletal β-TM to cTnT and may be a major determinant in modulating cardiac muscle performance and regulating Ca 2+ sensitivity of the myofilaments (196,200). Four mutations of the TM-encoding gene have been described in fHCM so far.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Most interesting, cells expressing the chimera retained normal microfilament architecture. More recent studies using transgenic expression of chimeras of ␣ and ␤ TMs have identified that the C terminal portion of TM is an important determinant of cardiac function (53).…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for this increased calcium sensitivity, we generated a double-transgenic mouse expressing a chimeric Tm containing the α-Tm amino terminus and the carboxyl terminus of β-Tm, the fetal cardiac isoform (Chi 1) (30). Previous work demonstrated that myofilaments from these Chi 1 mice have a decreased sensitivity to calcium (33,34). The double-transgenic mice which were created by crossing the 2 lines displayed normalized myofilament calcium sensitivity.…”
Section: Rescue Of Cardiomyopathic Mice By Contractile Proteinsmentioning
confidence: 99%